Influence of Air Temperature on Earning and Grain Yield of Durum Wheat - Bolqiev Zahid Toshtemirovich; Rustam Zakirjonovich Muradov; Panjiyeva Aziza Nodir qizi; Pardaeva Iroda Faxriddin qizi (Scientific Trends, 2022)
In this article Kashkadarya and Surkhondarya regions, which are the southern regions of the republic, in the conditions of air temperature, hard wheat new and rows the effect on the development phases, duration of the vegetation period and productivity indicators was studied.
Keywords: durum wheat, early maturity, yield, temperature, variety, comb, recoil, selection.